STUDI VARIASI MORFOLOGI POLLEN PADA BEBERAPA SPESIES DARI GENUS HIBISCUS - Hanum, Ulfah; Wahyuni, Sri; Susetyarini, Rr. Eko (Universitas Sebelas Maret, 2014)
Abstract- Genus Hibiscus is one of genuses in Family of Malvaceae which is spread out through seed, and its generative reproductive organ is flower. One part in flower are female gametophyte (pistil) and male gametophyte (stamen) which produce pollen. Plants that different species in same genus typically has different pollen. Variation in pollen morphology can be used as one of the value in taxonomy. This aims of research are investigating the variation of pollen’s layer morphology of some Hibiscus species. The method of current study is descriptive. Pollen which were investigated were from three species and one cultivare of Hibiscus, such as Hibiscus rosa-sinensis Mary Forbes, Hibiscus rosa-sinensis L. pink, Hibiscus rosa-sinensis L. yellow, Hibiscus tiliaceus L., dan Hibiscus schizopetalus Hook. f. The method which was used to observe pollen by SEM (Scanning Electron Microscope) with magnification 200x, 400x, and 1000x. Pollen has several characteristics which can be observed, such as aperture, pollen shape, pollen size, and type of exine ornamental. The analysis of data used descriptive qualitative.The result of this research showed that pollen some species of Hibiscus showed some variation pollen characteristics. P/E index of pollen 0.93 to 1.00, with the result the type of pollen shape are oblat spheroidal. Pollen grain size between 100 µm to 175 µm, but it have same type are permagna. The type of exine ornamental were echini, with different type, the lengthiest of echini is 20.6 µm in Hibiscus tiliaceus L., the withiest distance 40 µm of echini is Hibiscus rosa-sinensis L. yellow. Keywords: Genus Hibiscus, pollen, SEM